You need to move the decimal point to be at 1.
Since this is a decimal, the power will be negative.
I had to move the decimal 6 places.
So,
1^-6
I hope this helps!
~kaikers
<span>4 9/10 divided by 2 3/5
</span>4 9/10 = 49/10
2 3/5 = 13/5
so
(49/10) / (13/5)
=49/10 * 5/13
= 49/26
or
= 1 23/26
Answer:
$18,781.5
Step-by-step explanation:
According to the problem, calculation of the given data are as follows,
Loan amount (P) = $15,000
Rate of interest (r) = 23%
Time (t) = 5 years
Let this loan is compounding annually, then the amount after 5 years can be calculated as follows,
Final amount = P ![(1 + ( r/t))^{t}](https://tex.z-dn.net/?f=%281%20%2B%20%28%20r%2Ft%29%29%5E%7Bt%7D)
by putting the value in formula, we get
= $15,000 ( ![(1 + ( 0.23/5))^{5}](https://tex.z-dn.net/?f=%281%20%2B%20%28%200.23%2F5%29%29%5E%7B5%7D)
= $15,000 × 1.2521
= $18,781.5
Pytagorean theorem
height10
attached at 10-4=6 yards from bottom
8 yards from base to away
a^2+b^2=c^2
a and b are side legnths and c=hypotonuse
so therfore we are given a and b and we must solve for c
so
6=height
8=base
6^2+8^2=c^2
36+64=c^2
100=c^2
square root
10=c
so therfor the legnth of each cable is 10 yards
3 cables so 3 times 10=30
30 yards needed
For this case we have that by definition, the equation of the line in the slope-intersection form is given by:
Where:
m: It's the slope
b: It is the cut-off point with the y axis
By definition, if two lines are parallel then their slopes are equal.
We have the following line:
![-x + 3y = 6\\3y = x + 6\\y = \frac {1} {3} x + \frac {6} {3}\\y = \frac {1} {3} x + 2](https://tex.z-dn.net/?f=-x%20%2B%203y%20%3D%206%5C%5C3y%20%3D%20x%20%2B%206%5C%5Cy%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%20%5Cfrac%20%7B6%7D%20%7B3%7D%5C%5Cy%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%202)
Thus, the slope is:![m_ {1} = \frac {1} {3}](https://tex.z-dn.net/?f=m_%20%7B1%7D%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D)
Then ![m_ {2} = \frac {1} {3}](https://tex.z-dn.net/?f=m_%20%7B2%7D%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D)
So, the line is of the form:
![y = \frac {1} {3} x + b](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%20b)
We substitute the point
and find b:
![5 = \frac {1} {3} (3) + b\\5 = b](https://tex.z-dn.net/?f=5%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20%283%29%20%2B%20b%5C%5C5%20%3D%20b)
Thus, the equation is:
![y = \frac {1} {3} x + 5](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%205)
Answer:
![y = \frac {1} {3} x + 5](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%20%7B1%7D%20%7B3%7D%20x%20%2B%205)